Handbook of Positive Psychology, Religion, and Spirituality - Davis, Edward B.; Worthington Jr., Everett L.; Schnitker, Sarah A. (Springer International Publishing : Imprint: Springer, 2023)
This open access handbook aims to bridge the gap between the fields of positive psychology and the psychology of religion and spirituality. It is the authoritative guide to the intersections among religion, spirituality, and positive psychology and includes the following sections: (1) historical and theoretical considerations, (2) methodological considerations, (3) cultural considerations, (4) developmental considerations, (5) empirical research on happiness and well-being in relation to religion and spirituality, (6) empirical research on character strengths and virtues in relation to religion and spirituality, (7) clinical and applied considerations, and (8) field unification and advancement. Leading positive psychologists and psychologists of religion/spirituality have coauthored the chapters, drawing on expertise from their respective fields. The handbook is useful for social and clinical scientists, practitioners in helping professions, practitioners in religious and spiritual fields, and students of psychology and religion/spirituality. A comprehensive resource examining the intersections of positive psychology and the psychology of religion/spirituality Draws connections between two fields that research has increasingly shown to be connected "This Handbook provides a masterful, comprehensive review of theory, research, and clinical applications at the exciting intersection between the psychology of religion/spirituality and positive psychology. It demonstrates each of those fields is incomplete without the other. This book should be in the shelf of every serious student of religion, spirituality, and psychology." -Pehr Granqvist, Ph.D., Professor of Psychology, Stockholm University, Author of Attachment in Religion and Spirituality: A Wider View "Within this volume is found the next frontier of positive psychology, exponentially expanded through spiritual awareness and the translation of spiritual experience into lived positive cognition, behavioral habit, and practice. The editors of this volume help clear a rich new terrain for the next generation of humanitarian practitioners, researchers, and scholars." -Lisa Miller, Ph.D., Professor of Psychology and Education, Teachers College, Columbia University, Editor of Oxford University Press Handbook of Psychology and Spirituality, Author of The Awakened Brain and The Spiritual Child "At last! This broad-based, creative, integrative handbook helps fill a niche by focusing directly on the interface between positive psychology and the psychology of religion and spirituality." -Julie J. Exline, Ph.D., Professor of Psychology, Department of Psychological Sciences, Case Western Reserve University, Co-Author of Working With Spiritual Struggles in Psychotherapy: From Research to Practice.